How Managerial Ability and Board Profiles Drive Sustainability Perfomance: Evidence From Indonesia Manufacturing Firms - Tutik Siswanti (CONTABILITA : Journal of Accounting and Finance, 2025)
This study examines the influence of managerial competence and board characteristics on corporate sustainability performance, emphasizing the moderating role of green-oriented chief executive officers (CEOs). The research focuses on manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, using a purposive sampling technique to obtain 39 firm-year observations. Managerial ability is measured through efficiency-based financial indicators, while board characteristics are represented by directors’ accounting backgrounds and international experience. The study employs panel data regression analysis using EViews to test the proposed hypotheses. The empirical findings indicate that managerial ability and directors with international exposure significantly enhance corporate sustainability performance. In contrast, the proportion of board members with accounting backgrounds does not show a significant effect. Moreover, the moderating analysis reveals that the presence of green-oriented CEOs strengthens the positive association between managerial competence and sustainability outcomes. These results highlight the importance of leadership quality and global experience in fostering sustainable business practices within emerging markets. The study contributes to the growing literature on sustainable corporate governance and provides practical implications for firms aiming to integrate managerial capability and eco-conscious leadership into their strategic agenda